2009
DOI: 10.1002/hbm.20719
|View full text |Cite
|
Sign up to set email alerts
|

Separating function from structure in perfusion imaging of the aging brain

Abstract: The accuracy of the cerebral blood flow (CBF) imaging methods in humans has been impeded by the partial volume effects (PVE), which are a consequence of the limited spatial resolution. Because of brain atrophy, PVE can be particularly problematic in imaging the elderly and can considerably overestimate the CBF difference with the young. The primary goal of this study was to separate the structural decline from the true CBF reduction in elderly. To this end, a PVEcorrection algorithm was applied on the CBF imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 34 publications
(52 reference statements)
8
75
2
2
Order By: Relevance
“…In the current study, a direct relationship was observed between age and normative fitness, whereby younger participants exhibited poorer fitness relative to their peers than older participants. CBF in the precuneus declines with aging (Asllani et al 2009), and thus an age effect may have contributed to the inverse relationship between normative fitness and CBF.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, a direct relationship was observed between age and normative fitness, whereby younger participants exhibited poorer fitness relative to their peers than older participants. CBF in the precuneus declines with aging (Asllani et al 2009), and thus an age effect may have contributed to the inverse relationship between normative fitness and CBF.…”
Section: Discussionmentioning
confidence: 98%
“…But if a structural difference or some baseline blood flow difference is detected, how can we know whether these facts explain the BOLD signal differences? Moreover, if the size of the particular structure implicated is taken into account (Asllani et al, 2009), if different baseline levels that have been shown to affect the BOLD response are controlled for, if hormonal factors are balanced out, if contextual factors are manipulated, if. .…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In these previous ASL studies, no age-specific postlabeling delay was used, and the postlabeling delays that were used ranged from 800 to 1700 ms. PET and SPECT studies have revealed similar results. 9,10 Our findings confirm that pCBF decreases with age in healthy adults.…”
Section: Discussionmentioning
confidence: 99%